A rare example of the in situ formation of palladium nanoparticles: The emergence of catalytically active palladium nanoparticles from Pd (II) phosphine complexes in the Suzuki–Miyaura coupling reaction. (19th April 2022) - Altan, Orhan
Abstract : Suzuki–Miyaura coupling (SMC) reactions are one of the most promising routes for carbon–carbon bond formation. It is believed that metal complexes, particularly palladium complexes, are the most effective catalysts for this purpose. However, the catalysis nature whether it is homogenous or heterogeneous is under debate. It is commonly believed that a homogenous catalysis pathway is responsible for the catalytic activity when the phosphine ligands are present in the structure due to the strong phosphorus‐metal interactions. In this study, Pd (II) complexes of phosphino‐benzaldoxime ligands were synthesized, characterized, and tested in SMC reactions. Interestingly, it was found that the catalytic activity increased by 11 times when the amount of catalyst was reduced by 10‐fold and increased by five times when the amount of catalyst was decreased by 100‐fold. The detailed analyses revealed that the palladium nanoparticles (NPs) are responsible for the catalytic activity which was formed in the reaction medium. A plausible mechanism was proposed for the formation of Pd NPs from palladium phosphino‐benzaldoxime complexes in the reaction medium. This study is expected to contribute to the debate over whether the catalytic activity of phosphine‐palladium complexes in SMC reactions results from a homogeneous or heterogeneous pathway. Abstract : Because of the strong phosphorus‐metal interactions, it is commonly assumed that a homogeneous catalysis pathway is responsible for catalytic activity when phosphine ligands are present in the structure. In this study, Pd(II) complexes of phosphino‐benzaldoxime ligands were synthesized, characterized, and tested in Suzuki‐Miyaura coupling (SMC) reactions. They formed palladium nanoparticles (NPs) in the reaction medium, which are responsible for the catalytic activity. A plausible mechanism for the formation of Pd NPs has been proposed.